Síntese do éster de glicerol derivado do breu e suas aplicações - Penteado, Paula Scarabotto (Universidade Federal de São Carlos, 2022)
It is evident that the current world has become dependent on the use of plastic in several applications, among them, the use of resins has been widely explored in the construction, paints, varnish, adhesives and even jewelry and crafts sectors, as the epoxy resin. Currently, there is low recyclability of synthetic resins on a commercial scale, then, natural resins can be a great alternative for some applications. The glycerol ester is a derived resin from the esterification of rosin, in other words, of abietic acid, when in contact with the glycerol and an acid catalyst. This material is mainly applied in hot melt adhesives (solid materials that melt at low temperatures) and depilatory waxes since it has high sticking power and a relatively low softening point, which allows application at low temperatures. Abietic acid is a natural product found in pine trees, from which it can be extracted and, therefore, easily obtainable, making recycling much more effective.
Synthesis of glycerol ester derived from pitch and its applications
Keywords: Éster de glicerol; Breu; Derivados do breu; Esterificação; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA::QUIMICA DOS PRODUTOS NATURAIS